Psychosocial challenges faced by learners and the Neglect of School Social Work in Zimbabwe - Machimbidza, Dickson; Makhubele, Jabulani (Technium Social Sciences Journal, 2021)
Learners face a number of challenges in their eco-systems ranging from family related problems, bullying and ill-treatment at school. This study sought to examine the psychosocial challenges experienced by learners in Zimbabwe and the absence of school social work practice in Zimbabwe as well as the possible nexus between the two. The study embraced a qualitative research approach and used an qualitative exploratory-contextual design. A sample of 44 participants comprised of 16 learners, 12 parents/guardians, 10 social workers and 6 teachers participated in the study. The eco-systems theory and models of school social work served as the theoretical framework of the study. Purposive and convenience sampling techniques were used in identifying the participants for interviews and focus group discussions. The qualitative data were analyzed using thematic content analysis. It was found that learners face challenges of bullying, substance abuse, depression and anxiety as well as corporal punishment. Poor advocacy on school social work and lack of professional recognition by the government were found to be reasons behind the neglect of the practice in the country. It was established that late detection of warning signs is as a results of a nexus between the absence of school social work and psychosocial challenges among learners. Based on the findings of the study, the research recommends the recognition and employment of school social workers to deal with psychosocial challenges faced by learners. It further recommends social work regulatory boards to spearhead the acknowledgment of the profession through advocacy.